Functional characterization of the rice UDP-glucose 4-epimerase 1, OsUGE1: a potential role in cell wall carbohydrate partitioning during limiting nitrogen conditions. - David R Guevara; Ashraf El-Kereamy; Mahmoud W Yaish; Yong Mei-Bi; Steven J Rothstein (PLoS ONE)
Plants grown under inadequate mineralized nitrogen (N) levels undergo N and carbon (C) metabolic re-programming which leads to significant changes in both soluble and insoluble carbohydrate profiles. However, relatively little information is available on the genetic factors controlling carbohydrate partitioning during adaptation to N-limitation conditions in plants. A gene encoding a uridine-diphospho-(UDP)-glucose 4-epimerase (OsUGE-1) from rice (Oryza sativa) was found to be N-responsive. We developed transgenic rice plants to constitutively over-express the OsUGE-1 gene (OsUGE1-OX1-2). The transgenic rice lines were similar in size to wild-type plants at the vegetative stage and at maturity regardless of the N-level tested. However, OsUGE1-OX lines maintained 18-24% more sucrose and 12-22% less cellulose in shoots compared to wild-type when subjected to sub-optimal N-levels. Interestingly, OsUGE1-OX lines maintained proportionally more galactose and glucose in the hemicellulosic polysaccharide profile of plants compared to wild-type plants when grown under low N. The altered cell wall C-partitioning during N-limitation in the OsUGE1-OX lines appears to be mediated by OsUGE1 via the repression of the cellulose synthesis associated genes, OsSus1, OsCesA4, 7, and 9. This relationship may implicate a novel control point for the deposition of UDP-glucose to the complex polysaccharide profiles of rice cell walls. However, a direct relationship between OsUGE1 and cell wall C-partitioning during N-limitation requires further investigation.